2020
DOI: 10.1038/s42003-020-0860-1
|View full text |Cite
|
Sign up to set email alerts
|

Deep microbial proliferation at the basalt interface in 33.5–104 million-year-old oceanic crust

Abstract: The upper oceanic crust is mainly composed of basaltic lava that constitutes one of the largest habitable zones on Earth. However, the nature of deep microbial life in oceanic crust remains poorly understood, especially where old cold basaltic rock interacts with seawater beneath sediment. Here we show that microbial cells are densely concentrated in Fe-rich smectite on fracture surfaces and veins in 33.5-and 104-million-year-old (Ma) subseafloor basaltic rock. The Fe-rich smectite is locally enriched in organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 47 publications
5
37
0
Order By: Relevance
“…The greenish cell-like signals from the DNA dye and the overlapped NanoSIMS mapping of P and CN are consistent with results from previous study of microbial cells in mineral-filled cracks 9 . However, the appearance of individual cells was not clear, in contrast to the earlier work.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The greenish cell-like signals from the DNA dye and the overlapped NanoSIMS mapping of P and CN are consistent with results from previous study of microbial cells in mineral-filled cracks 9 . However, the appearance of individual cells was not clear, in contrast to the earlier work.…”
Section: Resultssupporting
confidence: 91%
“…Analytical procedures have been developed to visualize and quantify microbial cells hosted in crack-infilling minerals in the oceanic crust by preparing thin sections of rocks embedded in hydrophilic resin called LR White 8,9 . Microbial cells embedded in the resin are stainable with a DNA dye called SYBR-Green I.…”
Section: Resultsmentioning
confidence: 99%
“…Chemosynthetic DOC produced in situ is likely turned over rapidly in the shallow crustal fluids, but Δ 14 C values in the Deep horizon of U1383C suggest a net contribution of 14 C-enriched DOC from chemoautotrophy [10]. Two recent microbial studies of subseafloor rocks recovered via ocean drilling showed a dominance of heterotrophic bacteria and little evidence for autotrophic processes [57,58].…”
Section: Carbon Fixation and Turnovermentioning
confidence: 99%
“…However, these experiments also showed evidence for biomass production from DIC, and rates of activity varied over 8 orders of magnitude for both inorganic and organic carbon uptake, consistent with the mixotrophic genetic signatures observed in our study. Two recent microbial studies of subseafloor rocks recovered via ocean drilling also showed a dominance of heterotrophic bacteria and little evidence for autotrophic processes [58,59], suggesting mixotrophy and heterotrophy may be a common strategy in the cool, crustal subseafloor habitat.…”
Section: Carbon Fixation and Turnovermentioning
confidence: 99%